Realitas Perkawinan Beda Agama Perspektif Keluarga Sakinah - Nova Effenty Muhammad (Al-Mizan (e-Journal), 2020)
This paper concentrates on a happy family in Interfaith Marriage. According to the majority ulama, marriage is a theological activity that couple interfaith marriage will not a happy family. In this paper, I examine the interfaith marriage couple can be a happy family. Specifically, I ask how to concept a happy family according to the interfaith married couples? Further, how to manage family conflict on interfaith marriage for to get a happy family? To analyse a happy family on interfaith marriage couple, I use a qualitative analysis method with three approaches: Islamic law, sociology and psychology context. I use data collection methods with observation, interviews, and documents. This research argues that religion is not a major factor in a happy family because interfaith marriage can be a happy family. Worries Ulama that interfaith couples cannot be a happy family does not happen. The contribution of this study as the antithesis according to ulama about interfaith marriage, that happiness is not correlated with religion.